OPTIMIZATION OF SOME TECHNOLOGICAL PARAMETERS FOR FRESH CHILLI PRESERVATION BY CONTROLLED ATMOSPHERE METHOD - Tuan, Pham Anh; Mai, Le Thi (Vietnam Journal of Science and Technology, 2015)
The objective of this study was to optimize some parameters of fresh chili preservation technology by controlled atmosphere (CA) with 3 factors of corresponding surveyed domains: temperature (8 - 12 oC), concentration of oxygen (2 - 4 %) and concentration of carbon dioxide (3 - 6 %). Experimental plan includes 9 experiments following 23 plan repeating at center with the objective function as indicators of chili quality including total sugar content (%), organic acid content (%) and sensory quality (score). Nine experiments were concurrently conducted on a multifunction CA system in which parameters can be controlled and automatically monitored with good accuracy: temperature ± 0.5 oC, humidity ± 2 %, oxygen concentration ± 0.5 %, carbon dioxide concentration ± 0.5 %. The result was the successful determination of optimal experiment factors including temperature of 10.8 oC, oxygen concentration of 8 %, and carbon dioxide concentration of 6.0 %. The corresponding objective functions were achieved after 35 storage days with 3.65 % of total sugar content, 4.06 % of total organic acids, and good sensory quality (17.29/20 scores).